Students’ digital literacy practices: A close look at the border area - Canda Putri Anggini; Basran; Lisa Binti Harun; Lusy Rahmawati (English Learning Innovation, 2025)
The development of technology has changed the way people practice literacy including students at higher education levels, more specifically those who live on the borderline. This study was intended to investigate the digital literacy practices of polytechnic students on the borderline between Indonesia and Malaysia, addressing a significant gap in the existing literature that predominantly focuses on urban settings. Utilizing a mixed method design, data were collected from 135 students across various disciplines through questionnaires and interviews, framed around the eight components of digital literacy proposed by Hague and Payton (2010). Findings reveal that students exhibit a strong reliance on digital tools for academic and social purposes, with notable competencies in functional skills, creativity, collaboration, and cultural and social understanding. However, challenges remain in the ability to find and select information, critical thinking, and communication. The study highlights the importance of integrating comprehensive digital literacy education in higher education, emphasizing the need for targeted pedagogical strategies to enhance students' abilities to navigate the digital landscape effectively and safely. Overall, this study contributes to a deeper understanding of digital literacy practices in a unique geographical context, underscoring the interplay between technology use and educational outcomes among polytechnic students.